Collaborative Governance Challenges of the COVID-19 Pandemics: Czech Republic and Slovakia - Daniel Klimovsky; Ivan Maly; Juraj Nemec (Central European Public Administration Review)
The goal of this article is to evaluate what the Czech and Slovak governments have done to protect their countries and try to assess why they have achieved different results for the first and second waves of the Covid- 19 pandemic. The basis for such evaluation is the concept of collaborative governance, while qualitative research methods are used to achieve this goal. Based on comprehensive case studies and following analysis, the article suggests that in countries with limited quality of collaborative governance and no experience in similar pandemics, short-term “ultramobilisation” and positive results are indeed possible, but failures are non-avoidable in the long run. During the second wave of the pandemic, the weaknesses in governance resulted in massive governance failures. As a result, the governments’ responses delivered very limited results in terms of prevalence of Covid-19.